Lithium-metal battery degradation dataset from continuous cycling experimentsOSF - Maitri Uppaluri; Wenting Ma; Le Xu; Nojan Aliahmad; Alireza Saatchi; Karl Littau; Simona Onori (Data in Brief, 2025)
Lithium-metal batteries are promising next-generation batteries but but their limited lifetime and safety concerns remain key challenges for real-world deployment. The dataset presented in this paper contains current and voltage data, from which the capacity is calculated from 23 different lithium-metal battery cells, encompassing four different design configurations and nominal capacities. The cells were manufactured at Sakuu Corp., and the data were collected in its R&D laboratory. The cells underwent continuous cycling with a constant-current (CC) discharge and a constant-current constant-voltage (CC-CV) charge at different C-rates and voltage cutoffs at room temperature. Each cell experiences capacity loss from repeated cycling due to degradation mechanisms that lead to the formation of dead or inactive lithium, electrolyte depletion and increase in impedance during cycling. The voltage, current, and capacity data for each cycle are presented in the dataset. This dataset can be used for developing models and strategies to predict cell lifespan, accelerating design to improve performance and durability.